O aktualnostnočlenitveni stavi v slovenščini - Žele, Andreja (Jezik in slovstvo, 2018)
The article deals with phenomena related to functional sentence perspective in Slovenian. Recognising the functional sentence perspective as well as the significance of what is being communicated is crucial in setting transparent criteria for the formation of unambiguous and stylistically appropriate texts.
Keywords: besedni red; členitev po aktualnosti; informacijska nasičenost; informacijska nenasičenost; slovenščina; sporočilna perspektiva povedi